IMPLEMENTASI OTOMASI BERBASIS INTERNET OF THINGS (IoT) MENGGUNAKAN MIKROKOMPUTER UNTUK PEMANTAUAN IKLIM MIKRO RUMAH KACA - Nurpilihan Bafdal; Irfan Ardiansah (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2022)
The Internet of Things (IoT) is currently influencing many facets of human life. Smart agriculture is one system that can use the Internet of Things to improve production efficiency and consistency across agriculture, improve crop quality, and reduce negative environmental impacts. The architecture of an IoT-based microclimate monitoring system tailored for use with the Unpad ALG greenhouse is shown in this paper. The suggested system design can collect microclimate data using the SHT11 and GUVA-S12SD microclimate sensors and store it in a database on a Raspberry Pi with a cloud computing back-end idea. The Raspberry Pi is also used to process and analyze data in order to set up mist-based greenhouse cooling systems. The collected data is delivered to a web-based front-end node, which users can access from their own device. The results reveal that when the temperature rises beyond the predetermined threshold of 30°C or the humidity falls below 80%, the system can activate the mist-based cooling system. With a temperature difference of 6.25 degrees Celsius lower and humidity of 28.06 percent greater, the system is able to perform better than before it was introduced. The automation system's performance can be increased by 15.22%, however it will decline as the light intensity rises.